Effects of anodal transcranial direct current stimulation on motor evoked potentials variability in humans. Issue 13 (12th July 2019) - Bashir, Shahid; Ahmad, Shafiq; Alatefi, Moath; Hamza, Ali; Sharaf, Mohamed; Fecteau, Shirely; Yoo, Woo Kyoung
Abstract: Motor evoked potentials (MEPs) obtained from transcranial magnetic stimulation (TMS) allow corticospinal excitability (CSE) to be measured in the human primary motor cortex (M1). CSE responses to transcranial direct current stimulation (tDCS) protocols are highly variable. Here, we tested the reproducibility and reliability of individual MEPs following a common anodal tDCS protocol. In this study, 32 healthy subjects received anodal tDCS stimulation over the left M1 for three durations (tDCS‐T5, tDCS‐T10, and tDCS‐T20 min) on separate days in a crossover‐randomized order. After the resting motor threshold (RMT) was determined for the contralateral first dorsal interosseous muscle, 15 single pulses 4–8 sec apart at an intensity of 120% RMT were delivered to the left M1 to determine the baseline MEP amplitude at T0, T5, T10, T20, T30, T40, T50, and T60 min after stimulation for each durations. During TMS delivery, 3D images of the participant's cortex and hot spot were visualized for obtaining MEPs from same position. Our findings revealed that there was a significant MEPs improvement at T0 ( P = 0.01) after 10 min of anodal stimulation. After the 20‐min stimulation duration, MEPs differed specifically at T0, T5, T30 min ( P < 0.05). This indicates that tDCS is a promising tool to improve MEPs. Our observed variability in response to the tDCS protocol is consistent with other noninvasive brain stimulation studies. Abstract : Motor evoked potentials (MEPs) response are highly variable for anodal transcranial direct current stimulation (tDCS). The present study measured MEPs response over the left M1 for three durations (tDCS‐T5, tDCS‐T10, and tDCS‐T20 min) on separate days in a randomized order. We observed that the variability in response to the tDCS protocol is consistent with other noninvasive brain stimulation studies.